Administrative activity of law enforcement agencies of Ukraine (the procuracy of Ukraine and the sfs of Ukraine) - Гречанюк, Сергій; Пузирна, Наталія; Терещук, Галина; Гречанюк, Роксолана (Актуальні проблеми правознавства, 2017)
Administrative activity of law enforcement agencies of Ukraine (the procuracy of Ukraine  and the sfs of Ukraine)